2007
DOI: 10.1523/jneurosci.3699-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sites for Generation of Ectopic Spontaneous Activity in Neurons of the Chronically Compressed Dorsal Root Ganglion

Abstract: In a chronically compressed dorsal root ganglion (CCD) in the rat, a model of foraminal stenosis and radicular pain in human, a subpopulation of neurons with functional axons exhibits spontaneous activity (SA) that originates within the ganglion. Intracellular electrophysiological recordings were obtained from the somata of neurons of the compressed ganglion both in vitro and in vivo. The SA was classified into two types according to the presence (type I) or absence (type II) of subthreshold membrane potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 48 publications
(69 reference statements)
6
108
0
2
Order By: Relevance
“…Foraminal stenosis encompasses some of the most common and popular reasons that are used to explain acute and chronic sciatica. Under CCD conditions, spontaneous action potentials can originate from multiple locations in both the soma and the axons of the DRG neurons and these spontaneous action potentials may alter the transmission of sensory information from peripheral receptors [12]. According to this etiology, the paw withdrawal frequency by either mechanical or cold stimuli was significantly increased following CCD surgery as compared with that of the sham operative animals in our study.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Foraminal stenosis encompasses some of the most common and popular reasons that are used to explain acute and chronic sciatica. Under CCD conditions, spontaneous action potentials can originate from multiple locations in both the soma and the axons of the DRG neurons and these spontaneous action potentials may alter the transmission of sensory information from peripheral receptors [12]. According to this etiology, the paw withdrawal frequency by either mechanical or cold stimuli was significantly increased following CCD surgery as compared with that of the sham operative animals in our study.…”
Section: Discussionmentioning
confidence: 48%
“…Several lines of evidence have suggested that the origin of spontaneous activity in the CCD was most likely the soma rather than the axons or the terminal endings [12]. Differing alterations of sodium currents in small dorsal root ganglion neurons have also been observed after CCD and sciatic nerve injury [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have now shown, K Na channels are abundantly and ubiquitously expressed in DRG neurons. Since both propioceptors and nociceptors are believed to contribute to painful neuropathy (Amir et al, 1999;Ma and LaMotte, 2007), K Na channel dysfunctioning may be a likely culprit in the pathology of neuropathic pain. Alternatively, increasing K Na channel activity may also represent a therapeutic strategy for the treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The base plate holding the animal was then mounted to a frame under the objective of an upright microscope (BX51WI; Olympus Optical, Tokyo, Japan). The neurons on the surface of DRG were viewed through a ϫ40 water-immersion objective (magnification ϫ400) using reflective microscopy via an analyzer-50/50 mirror-polarizer set (Ma and LaMotte 2007). The DRG was continuously superfused by oxygenated ACSF at a rate of 3 ml/min, and the temperature was maintained at 37 Ϯ 0.5°C via an in-line heater (TC-344A; Warner Instrument, Hamden, CT).…”
Section: Animalsmentioning
confidence: 99%